2017
DOI: 10.1186/s12943-017-0591-1
|View full text |Cite
|
Sign up to set email alerts
|

CD73/NT5E is a target of miR-30a-5p and plays an important role in the pathogenesis of non-small cell lung cancer

Abstract: BackgroundCD73 (ecto-5′-nucleotidase) is implicated in the development of many types of cancer. CD73 inhibitors are currently being tested in clinical trials for the treatment of cancer. Understanding the molecular and cellular actions of CD73 inhibitors is the key to improving this line of therapy.MethodsQuantitative real-time PCR (qRT-PCR) was used to detect the expression of CD73 and miR-30a-5p; Western blot and immunohistochemical assays were used to investigate the levels of CD73 and other proteins. Flow … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
136
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 137 publications
(142 citation statements)
references
References 44 publications
6
136
0
Order By: Relevance
“…Furthermore, in patients with EGFR mutation‐negative NSCLC, expression of CD73 was not associated with the outcome of treatment with ICIs, unlike the situation in patients who were EGFR mutation‐positive. Our findings appear to be consistent with those of previous preclinical studies, which have shown that the mechanism of CD73‐induced immune tolerance involves the EGFR signaling pathway …”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, in patients with EGFR mutation‐negative NSCLC, expression of CD73 was not associated with the outcome of treatment with ICIs, unlike the situation in patients who were EGFR mutation‐positive. Our findings appear to be consistent with those of previous preclinical studies, which have shown that the mechanism of CD73‐induced immune tolerance involves the EGFR signaling pathway …”
Section: Discussionsupporting
confidence: 92%
“…MiRNA array data from our previous study showed that 15 miRNA expressions were significantly upregulated in lung carcinoma compared to normal lung tissues A).…”
Section: Resultsmentioning
confidence: 96%
“…MiRNA array data from our previous study showed that 15 miRNA expressions were significantly upregulated in lung carcinoma compared to normal lung tissues. 6,21 More specifically, seven miRNAs (miR-183-5p, miR-193b-3p, miR-210, miR-21-5p, miR-224-5p, miR-4286, and miR-96-5p, log2 fold change ≥2.0, P < 0.05) were upregulated ( Figure 1A). Among these, miR-210 and miR-21-5p have been reported to be significant diagnostic markers in NSCLC.…”
Section: Mir-4286 Expression Is Upregulated In Nsclc Tissues and Cementioning
confidence: 99%
“…Cell motility was analyzed as previously described . Briefly, for the wound‐healing assay, cells were seeded in six‐well plates 48 h after transfection to form a monolayer.…”
Section: Methodsmentioning
confidence: 99%